The powers to lead - Nye, Joseph S. (Oxford Oxford University Press, 2008)
What qualities make a leader succeed in business or politics? In an era when the information revolution has dramatically changed the playing field, when old organizational hierarchies have given way to fluid networks of contacts, and when mistrust of leaders is on the rise, our ideas about leadership are clearly due for redefinition.
Includes bibliographical references (p. [183]-206) and index.
Keywords: Political leadership